(450) Classification of Industries In Social Countries تصنيف الصناعات في الدول الاجتماعية - Engert, Manfred (The Institute of National Planning, 2025)
This study examines the classification of industries in socialist countries as a fundamental instrument supporting economic planning and statistical systems. The study is based on the assumption that effective national planning requires a standardized classification framework for economic activities and industrial products in order to facilitate data collection, aggregation, analysis, and comparison at both national and international levels. The study explains that economic planning relies heavily on quantitative information related to production activities, resources, and economic sectors. Consequently, the classification of industries and products becomes essential for ensuring consistency between statistical information and planning objectives. Within this context, the study reviews the experience of the Council for Mutual Economic Assistance (CMEA), whose member countries developed a unified classification system designed to improve economic coordination and integration among participating states. Furthermore, the study demonstrates that the proposed classification framework is based on grouping economic activities according to technological and production characteristics. The system identifies sixteen major industrial branches, including energy production, mining, metallurgy, machinery manufacturing, chemical industries, construction materials, textiles, food industries, and other productive sectors. Such classification facilitates the organization and interpretation of economic data and supports broader planning activities. The study also discusses the principles used for product classification, including final use, raw material characteristics, and technological production processes. Particular emphasis is given to the coding system used to identify sectors, industrial branches, and products with precision and consistency. The study concludes that a unified industrial classification system represents a necessary prerequisite for comprehensive economic planning. Such a system contributes to improved statistical accuracy, more efficient commodity balance analysis, stronger international economic coordination, and more effective development decision-making processes.